WATAK PROTAGONIS TOKOH RIRI DALAM NOVEL SAAT HATI TELAH MEMILIH KARYA MIRA W - Abdoel Gafar; Nina Maryani (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this research is to describe the aspect of  protagonist character in the novel Saat Hati Telah Memilih. The aspect of the protagonist in the character of Riri in the novel Saat Hati Telah Memilih  represents the aspect of honest, humble, clever, independent and defender. This research is qualitative research. This research is used to understand phenomenon in the subject of the research by the decription of words and language by using the data. The data is in the forms of quotations of aspect of protagonist character Riri in the novel Saat Hati Telah Memilih. The result of the research is the description of some aspects of protagonist character of Riri in the novel Saat Hati Telah Memilih. From the total of 52 quotations, it can be found that there are 11 expressions of honesty aspect, 25 expressions of humble aspect, 8 expressions of smart aspect, 3 expressions of independent aspect, and 5 expressions of defender aspect. The most dominant aspect of the protagonist character is considerate, humble, generous, and care.